Motivation in multimodal classroom learning: an empirical study of business English learners in China - Wang, Jianna; Hassan, Hanita (2023)
The importance and complexity of motivation as a component in second language acquisition have long been recognized. As multimedia and ICT technology advances, more researchers are paying special attention to how language learners might maintain motivation in a multimodal classroom setting. The purpose of this article mainly investigates the L2 motivation in Business English learners’ interlanguage talk in terms of motivation orientation, attitude, desire and effort in multimodal classroom learning. The empirical investigation employed the Attitude/Motivation Test Battery (AMTB) of Gardner’s and interview to attach importance on three questions: a) What is the motivational state of Business English learners in multimodal classroom teaching? b). What is the relationship between motivation and competence of interlanguage talk? c) What are the strategies for triggering the motivation of learners in multimodal classroom teaching? And the findings can be drawn from the study that the Business English learners are motivated more intrinsically than extrinsically in interlanguage talk due to the strong interest and L2 vision. The students have strong desire and positive attitude to improve their oral English competence in multimodal classroom learning. However, although they also have the consciousness in effort, there is still lace of persistence. This article then indicates that triggering the motivation can enhance the students’ competence of interlanguage talk in multimodal classroom learning. Consequently, the empirical study implies for the teachers that designing the group-project teaching in multimodal classroom teaching can stimulate the students’ motivation and improve their English competence development. Moreover, it encourages the teachers to design more scientific and rational multimodal pedagogic in the class.